Verisyse versus Veriflex Phakic Intraocular Lenses: Refractive Outcomes and Endothelial Cell Density 5 Years after Surgery - Dilek Yaşa; Alper Ağca (Journal of Ophthalmology)
Purpose. To compare refractive stability, central endothelial cell density (ECD), and complications between Verisyse (Abbott Medical Optics, Netherlands) and Veriflex (Abbott Medical Optics, Netherlands) phakic intraocular lenses (pIOL) over five years. Methods. We retrospectively reviewed the medical records of patients who underwent Verisyse or Veriflex pIOL implantation for surgical correction of myopia. Patients with a 5-year follow-up period were included in the study. Uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), spherical equivalent of manifest refraction (SE), and ECD were compared between the groups preoperatively and 1, 3, and 5 years postoperatively. Results. The study included 47 eyes in the Verisyse group and 50 eyes in the Veriflex group. There was no significant difference in mean SE, UDVA, CDVA, and ECD preoperatively or postoperatively. In both groups, there was a statistically significant myopic shift between 1-year and 5-year visits (−0.25 ± 0.30 D and −0.23 ± 0.48 D in the Verisyse and Veriflex groups, respectively). There was no significant difference between the groups in terms of efficacy and safety indexes at 5 years. ECD loss was highest during the first year (3.9% loss in the Verisyse group and 3.9% loss in the Veriflex group, p=0.670). At 5 years, the mean cumulative ECD losses in the Verisyse and Veriflex groups were 7.42% and 7.64%, respectively (p=0.709). Cataracts developed in 2.1% of the eyes in the Verisyse group and in 2.0% of those in the Veriflex group. No sight-threatening complications were observed. Conclusion. Verisyse and Veriflex pIOLs are highly effective for treating high myopia up to 5 years after surgery. Longitudinal studies with longer follow-up periods are necessary to determine the endothelial safety profile.